Critical patient environmental comfort: a scoping review protocol - Moura, Derek; Andrade, Débora; Silva, Carla; Pinto, Igor (Millenium - Journal of Education, Technologies, and Health, 2023)
Introduction: It is important to understand the concept of comfort as a whole in order to build a care intervention plan that is appropriate to the needs of the patient. A quiet and peaceful environment enhances the person's adherence to treatment, which allows better outcomes. Objectives: To map the nursing interventions that promote environmental comfort to the sleep of the critically ill person; to identify indicators and tools to assess the sleep of the critically ill person. Methods: Literature review, based on the methodological strategy of the Joanna Briggs Institute for Scoping Reviews. The databases used will be: CINAHL Complete, COCHRANE Library Plus, PUBMED, JBI Evidence Synthesis, Scientific Electronic Library Online (SciELO); and as sources of gray literature: OpenGrey, Open Access Scientific Repositories in Portugal (RCAAP). Results: With this scoping review it is hoped to map nursing interventions that contribute to environmental comfort and sleep promoting in people in intensive care and in critical condition, as well as indicators and tools to assess sleep. Conclusion: The development of knowledge about nursing interventions in the context of critical care will allow the maping of a set of interventions that focus on promoting the comfort of the person in critical situation.